DESKRIPSI PEMAHAMAN KONSEP MATEMATIKA PADA MATERI BANGUN RUANG SISI LENGKUNG - Khardiyawan A.Y. Pauweni; Kartin Usman; Abdul Wahab Abdullah; Rusydiy Rusydiy (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2019)
This research is a descriptive study with a qualitative approach to analyze the understanding of mathematical concepts on the curved side of the building material. The research was conducted at SMP Negeri 2 Kabila involving 21 students as research subjects. Indicators used to describe students' understanding of mathematical concepts include (1) restating a concept, (2) Classifying objects according to certain properties according to the concept, (3) Presenting concepts in various forms of mathematical representation, (4) Applying problem-solving concepts or algorithms, written tests. Furthermore, interviews were conducted to deepen information about students' understanding of mathematical concepts. The results of the analysis showed that the students 'understanding of mathematical concepts on the curved side of the building material was classified as moderate, which was shown by the students' ability that only fulfilled part of the indicators of understanding the measured mathematical concepts.